Analysis of the value chain of freeze-dried coffee through the Delphi methodology and competitive proposals - Carpio Espino, Sebastian Mauricio (2024)
Currently, the Peruvian lyophilized coffee value chain has a discrete participation with respect to its competitors in the international market. The main objective of the research was to analyze the value chain of Peruvian lyophilized coffee, identifying comparative and competitive advantages in international markets. The methodology used was a mixed approach with a quasi-experimental design. Based on the current value chain mapping and the current design of the supply chain of Peruvian lyophilized coffee, it was possible to analyze with greater precision the main problems presented by the links that make up the value chain, in order to design a model that generates value proposals in the production and commercialization of Peruvian coffee, and that are capable of contributing to the competitiveness of Peruvian lyophilized coffee in international markets.